Open- and closed-loop responses of joint mechanisms in perturbed stance under visual and cognitive interference. (April 2018) - Ashtiani, Mohammed N.; Azghani, Mahmood-reza
Highlights: The stabilogram-diffusion analysis was used kinematic features of perturbed balance. Hip strategy used the sensory feedback with delay rather than the ankle and knee. Addition of an arithmetic cognitive load reduced the stability. The whole body sway was not harmonized with contribution of the joint strategies. Abstract: Balance control requires sensory information to properly adjust the posture against the applied perturbation in which the early responses may not use the sensory feedback. Stabilogram-diffusion analysis (SDA) was developed to distinguish the open- and closed-loop modes of postural control based on routine standing indices. This study was aimed at evaluating the roles of visual and cognitive interference on regulations of the joint strategies. Sixteen healthy young males were stood on a rotating support with open and closed eyes and with and without cognitive interference (total four sensory conditions). Motion analysis was employed to obtain kinematic changes in the body. In addition to calculating some classical metrics (path length, range of joint motion, etc), the SDA was applied to the kinematics of the center of mass and lower limb joints to determine how they use sensory information during perturbed stance. Effects of vision were merely observed in the classical stance parameters, but the cognitive loads influenced the SDA ones. The joint mechanisms revealed totally different behaviors during the short- and long-term regions ( p < 0.016) and the time interval and squared angles while starting to acquire sensory information ( p < 0.030). Cognitive loads reduced the stability of standing by increasing the short-term diffusion coefficients ( p = 0.015). Application of the SDA could present some details about the sensory-dependent behaviors of the joint strategies.